Fluid-Phase Pinocytosis of LDL by Macrophages: A Novel Target to Reduce Macrophage Cholesterol Accumulation in Atherosclerotic Lesions - Kruth, Howard S. (Curr Pharm Des, 2013)
Circulating low-density lipoprotein (LDL) that enters the blood vessel wall is the main source of cholesterol that accumulates within atherosclerotic plaques. Much of the deposited cholesterol accumulates within plaque macrophages converting these macrophages into cholesterol-rich foamy looking cells. Cholesterol accumulation in macrophages contributes to cholesterol retention within the vessel wall, and promotes vessel wall inflammation and thrombogenicity. Thus, how macrophages accumulate cholesterol and become foam cells has been the subject of intense investigation. It is generally believed that macrophages accumulate cholesterol only through scavenger receptor-mediated uptake of modified LDL. However, an alternative mechanism for macrophage foam cell formation that does not depend on LDL modification or macrophage receptors has been elucidated. By this alternative mechanism, macrophages show receptor-independent uptake of unmodified native LDL that is mediated by fluid-phase pinocytosis. In receptor-independent, fluid-phase pinocytosis, macrophages take up LDL as part of the fluid that they ingest during micropinocytosis within small vesicles called micropinosomes, and by macropinocytosis within larger vacuoles called macropinosomes. This produces cholesterol accumulation in macrophages to levels characteristic of macrophage foam cells in atherosclerotic plaques. Fluid-phase pinocytosis of LDL is a plausible mechanism that can explain how macrophages accumulate cholesterol and become disease-causing foam cells. Fluid-phase pinocytosis of LDL is a relevant pathway to target for modulating macrophage cholesterol accumulation in atherosclerosis. Recent studies show that phosphoinositide 3-kinase (PI3K), liver X receptors (LXRs), the macrophage colony-stimulating factor (M-CSF) receptor, and protein kinase C (PKC) mediate macrophage macropinocytosis of LDL, and thus, these may be relevant targets to inhibit macrophage cholesterol accumulation in atherosclerosis.